Predicting the geographical distribution and niche characteristics of Cotoneaster multiflorus based on future climate change - Huang, Qiuliang; Liu, Haoyang; Li, Changshun; Zhu, Xiaoru; Yuan, Zongsheng; Lai, Jialiang; Cao, Minghui; Huang, Zhenbei; Yang, Yushan; Zhuo, Shenglan; Lü, Zengwei; Zhang, Guofang (Frontiers in Plant Science, 2024)
Introduction: Arid and semi-arid regions are climate-sensitive areas, which account for about 40% of the world's land surface area. Future environment change will impact the environment of these area, resulting in a sharp expansion of arid and semi-arid regions. Cotoneaster multiflorus is a multifunctional tree species with extreme cold, drought and barren resistance, as well as ornamental and medicinal functions. It was found to be one of the most important tree species for ecological restoration in arid and semi-arid areas. However, bioclimatic factors play an important role in the growth, development and distribution of plants. Therefore, exploring the response pattern and ecological adaptability of C. multiflorus to future climate change is important for the long-term ecological restoration of C. multiflorus in arid and semi-arid areas. Methods: In this study, we predicted the potential distribution of C. multiflorus in China under different climate scenarios based on the MaxEnt 2.0 model, and discussed its adaptability and the major factors affecting its geographical distribution. Results: The major factors that explained the geographical distribution of C. multiflorus were Annual precipitation (Bio12), Min air temperature of the coldest month (Bio6), and Mean air temperature of the coldest quarter (Bio11). However, C. multiflorus could thrive in environments where Annual precipitation (Bio12) >150 mm, Min air temperature of the coldest month (Bio6) > -42.5℃, and Mean air temperature of the coldest quarter (Bio11) > -20℃, showcasing its characteristics of cold and drought tolerance. Under different future climate scenarios, the total suitable area for C.multiflorus ranged from 411.199×10 4 km² to 470.191×10 4 km², which was 0.8~6.14 percentage points higher than the current total suitable area. Additionally, it would further shift towards higher latitude.Discussion: The MaxEnt 2.0 model predicted the potential distribution pattern of C. multiflorus in the context of future climate change, and identified its ecological adaptability and the main climatic factors affecting its distribution. This study provides an important theoretical basis for natural vegetation restoration in arid and semi-arid areas.